Building online social identity and fandom activities of K-pop fans on Twitter - Marlyna Maros,; Fara Nadia Abdul Basek, (Penerbit Universiti Kebangsaan Malaysia, 2022)
K-pop fans are widely known to use social media as a platform for their activities. Over the years, they have built online communities, which are called fandoms. K-pop fandoms are zealous in fandom activities that some abused were detected, such as spreading false news and provocating fandom wars. These could potentially lead to cyberbullying and damage the quality of online social interaction. The fans are not careful about their actions as they are using the online social identity. Thus their real identity is saved. Hence, the purposes of this study are to analyse the online social identity of K-pop fandom members, how they were introduced to the K-pop world and the purpose(s) of the fandom activities. A total of 30 participants were interviewed online for this study. Thematic analysis of the interview was done based on three stages of Tajfel’s Social Identity Theory (1979) which is (1) characteristic, (2) social identification, and (3) social comparison, and Bennett’s Four Areas of Fandom (2014) which are (1) communication, (2) creativity, (3) knowledge and (4) civic power and organisation. The findings of this research revealed six characteristics of the fans’ online social identity as K-pop fans, the influential factors that introduced them to K-pop, and details on their fandom activities. This study provides insights into the online social identity of K-pop fans and fandom activities on Twitter. Further research is recommended to explore the language used by the K-pop community for inter- and intra-group communications, which will further enrich the understanding of this online social community.